THE EFFECTIVENESS OF FLIPPED CLASSROOM MODEL BY USING GOOGLE CLASSROOM APPLICATION TO INCREASE STUDENTS’ LISTENING SKILL - Wafiqah, Nurul; ul Haq, Muhammad Zia; Sangkala, Ismail (FKIP Unismuh Makassar, 2024)
The purpose of this study was to find out whether the Flipped Classroom model with the Google Classroom application increase student learning outcomes in listening skills at SMKN 6 Bone. This study used a quasi-experimental method with a nonequivalent control group designed and applied in two classes with two different learning models. Experimental classes with the Flipped Classroom model using the Google Classroom application and control classes with the Teacher Centered Learning model. The population of this study was 114 students of class X of SMKN 6 Bone, while the sample consisted of 60 students from the initial three classes who were given pretests to determine which classes had balanced abilities to be used as experimental classes and control classes. The research process is carried out with the following procedures: giving pretest, applying treatment, and giving posttest. From the results of the posttest descriptive analysis, it is known that there are significant differences between the control class and the experimental class. This is evident from the from posttest result with p-value 0.03 (sig. <0.05). In addition, based on inferential gain analysis, it is known that p-value = 0.02 which means there are significant differences from the results of the pretest and posttest. So, it was concluded that the use of the Flipped Classroom model with Google Classroom application is effective to increase students' listening skills.